Weight loss in pregnancy and cardiometabolic profile in childhood: findings from a longitudinal birth cohort. (22nd August 2014) - Grooten, IJ; Painter, RC; Pontesilli, M; van der Post, JAM; Mol, BWJ; van Eijsden, M; Vrijkotte, TGM; Roseboom, TJ
<x xml:space="preserve">Abstract</x> Objective To investigate the consequences of weight loss in pregnancy on pregnancy outcomes and cardiometabolic profile in childhood. Design Prospective birth cohort (ABCD study). Setting Between 2003 and 2004, all pregnant women in Amsterdam were approached for study participation. Population 7818 pregnant women were included, of which 3165 consented to having their children examined at 5–6 years of age. In 1956 children fasting capillary blood samples were also taken. Methods At antenatal booking, women answered questions about their pregnancy and whether they suffered from severe weight loss (SWL; >5 kg). Pregnancy details and outcomes were available through the obstetric caregiver. Main outcome measures At birth main outcome measures were prematurity (<37 weeks) and birthweight. At follow‐up, body mass index (BMI), blood pressure, glucose and lipids were assessed. Results SWL occurred in 6.8% of cases. Women with SWL had similar preterm birth rates compared with women without these complaints (adjusted OR 1.1, 95%CI 0.7, 1.7). Birthweight (adjusted difference – 31 g, 95%CI −76, 15) and BMI at 5–6 years of age (adjusted difference 0.2 kg/m2, 95%CI 0.0, 0.5) were similar in children born to mothers with SWL and without SWL, but blood pressure was increased. For diastolic blood pressure this association was independent of confounders (adjusted difference 1.4 mmHg, 95%CI 0.4, 2.4). Lipid and glucose levels were not significantly different between these groups. Conclusion Early pregnancy weight loss, usually occurring as a manifestation of hyperemesis gravidarum, could have long‐term consequences for offspring health.